2016
DOI: 10.21058/gjecs.2016.11001
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Based Efficient Design of Traffic Light Controller using Frequency Scaling for Family of HSTL

Abstract: Traffic blockage is one of the major issues faced by world today. That can be road traffic or air traffic or even water traffic .Traffic Controllers provide the right direction by providing a rule for any kind of Vehicles. The idea goes around designing traffic light controller system which utilizes least amount of power and is well tested in hardware using Xilinx Virtex6 Field Programmable gate array. FPGA designs are not only cheaper than ASIC designs but have many positive features like speed and performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Sharma et al [10] suggested an fine-pitch ball grid array (FBGA) based traffic light controller architecture. In comparison to other design methods, the author believed that using FPGA minimized power consumption.…”
Section: Conventional Design Approachmentioning
confidence: 99%
“…Sharma et al [10] suggested an fine-pitch ball grid array (FBGA) based traffic light controller architecture. In comparison to other design methods, the author believed that using FPGA minimized power consumption.…”
Section: Conventional Design Approachmentioning
confidence: 99%